The Beekeeping State and Inventory of Mellifero-Medicinal Plants in the North-Central of Morocco - Meryem Bakour; Hassan Laaroussi; Nawal El menyiy; Tarik Elaraj; Asmae El ghouizi; Badiaa Lyoussi (The Scientific World Journal)
This study aims to determine the diversity of melliferous plants and to recognize the state of beekeeping in the Fez-Meknes region in Morocco. We conducted a questionnaire for beekeepers that set up their hives in the prefectures and provinces of the region, and we have studied the pharmacological evidence of the most preferred plants by beekeepers to assess its medicinal values. The results indicate that honey, bee pollen, bee bread, royal jelly, propolis, bee wax, bee venom, and bee queens are produced in this region with different percentages, and 102 plants belonging to 32 families were obtained in the inventory of melliferous plants; the most represented families were Asteraceae and Lamiaceae (13.73% each) followed by Rosaceae (8.82%). Among these 102 plants identified, 79 plants provide nectar and pollen for bees, 16 plants provide only pollen, 3 plants provide only nectar, 35 plants are resinous, and 6 plants provide honeydew for bees. The outcome of this study will contribute to the valuation of melliferous plants and help to establish a practical guide for the development of the beekeeping sector as an agricultural economic approach.